2016
DOI: 10.1111/1744-7917.12329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphometric and chemical analyses of phenotypes of two invasive ambrosia beetles (Euwallacea spp.) in the United States

Abstract: The polyphagous shot hole borer (PSHB), Euwallacea sp., was first detected in 2003 in Los Angeles County, California, USA. Recently, this invasive species has become a major pest of many hardwood trees in urban and wildland forests throughout southern California. PSHB is nearly identical in morphology and life history to the tea shot hole borer (TSHB), Euwallacea fornicatus, an invasive pest of hardwoods in Florida, USA and many other parts of the world. However, molecular studies have suggested that the taxa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The chemical and behavioral data presented here indicates that these morphologically indistinguishable beetles, carrying different species of symbiotic Fusarium , and originating from three different invasive populations, have formed pheromone races, and further supports the amassing evidence that they have speciated into three cryptic species ( Kasson et al, 2013 ; O’Donnell et al, 2015 ; Chen et al, 2016 ; Stouthamer et al, 2017 ). According to Stouthamer et al (2017) , multiple haplotypes were found of PSHB in Vietnam and Taiwan, of KSHB in Taiwan and Okinawa, and of TSHB in Thailand and India, suggesting their possible native origins.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The chemical and behavioral data presented here indicates that these morphologically indistinguishable beetles, carrying different species of symbiotic Fusarium , and originating from three different invasive populations, have formed pheromone races, and further supports the amassing evidence that they have speciated into three cryptic species ( Kasson et al, 2013 ; O’Donnell et al, 2015 ; Chen et al, 2016 ; Stouthamer et al, 2017 ). According to Stouthamer et al (2017) , multiple haplotypes were found of PSHB in Vietnam and Taiwan, of KSHB in Taiwan and Okinawa, and of TSHB in Thailand and India, suggesting their possible native origins.…”
Section: Discussionsupporting
confidence: 78%
“…Each of these three beetle species carry different species of symbiotic Fusarium in their mandibular mycangia ( O’Donnell et al, 2015 ; Carrillo et al, 2016 ), and the inability of PSHB and TSHB larvae to survive when fed Fusarium from the other species suggests that isolation between species also takes place in their obligatory feeding requirements for their associated Fusarium species as well ( Freeman et al, 2013a ). Differences were also found between the cuticular hydrocarbon profiles of PSHB and TSHB which could potentially assist in species diagnostics since they are morphometrically indistinguishable ( Chen et al, 2016 ). These three cryptic species are similar in their polyphagous nature, in that they can attack and spread their Fusarium symbiont to hundreds of tree species in numerous families ( Danthanarayana, 1968 ; Eskalen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The different lineages are supported by rapidly evolving mitochondrial genes and more conserved nuclear gene regions. Although these potential different species display morphological differences, reliable morphological diagnosis has not been established (Chen et al 2016). …”
Section: Systematicsmentioning
confidence: 99%
“…2;O'Donnell et al 2015), because of their morphological similarity (Eskalen et al 2013;Chen et al 2017). However, DNA sequences from mitochondrial cytochrome oxidase c subunit 1 (COI) and cuticular hydrocarbon profiles support the status of PSHB and TSHB as separate taxa (O'Donnell et al 2015;Chen et al 2017;Stouthamer et al 2017). Stouthamer et al (2017) reported that the native range of PSHB may encompass Northern Thailand, Vietnam, China, Taiwan, and Okinawa.…”
Section: Introductionmentioning
confidence: 99%
“…5;O'Donnell et al 2015, Gomez et al 2018b, is a second exotic ambrosia beetle that was first detected in 2013 in urban forests of San Diego County (Chen et al 2017;Stouthamer et al 2017). KSHB is similar morphologically to PSHB and TSHB but differs in cuticular hydrocarbon phenotype (Chen et al 2017) and in DNA sequence from the COI region (Stouthamer et al 2017); it also carries novel Fusarium sp. and Graphium sp.…”
Section: Introductionmentioning
confidence: 99%